The Influence of Flashsale, Bundling Products, and Social Media Marketing on Skintific Skincare Purchase Decision in Skintific Official Shop According to Islamic Business Perspective: (Study on Consumers of Tiktok Shop Users in Bandar Lampung) - Sofiana, Ananda Mery; Zulaikah; Susanti, Yeni (International Publisher (YAPENBI), 2025)
The purpose of this study is to examine the impact of flash sales, bundling products, and social media marketing on purchasing decisions of Skintific skincare at the Skintific Official Shop on TikTok Shop in Islamic business perspective. A quantitative approach with a purposive sampling strategy and a sample size of 100 respondents was used to study Bandar Lampung customers. Respondents who had bought Skintific products through TikTok Shop were given questionnaires to complete in order to gather data, and the Smart-PLS program was used for analysis. The association between the independent factors (social media marketing, flash sales, and product bundling) and the dependent variable (buying decision) was investigated using multiple linear regression analysis. The findings indicate that flash sale, social media marketing, and product bundling significantly and favourably influence consumers' decisions to buy. In order to improve customer purchase decisions, business practitioners can use the findings from this study to optimise digital marketing techniques in line with Islamic business principles.